(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Manual bag-valve-mask (BVM) ventilation is a critical emergency response technique; however, studies show that practitioners often deliver unsafe tidal volumes (tV), pressures, and breath rates, increasing the risk of lung injury, gastric inflation, or hypoxia. This study developed an automated BVM system to ensure accurate and consistent positive pressure ventilation (PPV) while providing real-time monitoring of tidal volume, peak pressure, and breath rate. The system integrates a stepper motor-driven compression mechanism, an orifice-based flow sensor, and an LCD interface for user adjustments and real-time feedback. Testing demonstrated that the automated system successfully maintained ventilation within a safe range, with tidal volume values deviating by no more than 100 mL from calibrated Douglas Bag measurements. Stepper motor-controlled compression exhibited a linear relationship with tidal volume, with optimal airflow delivery occurring between 90° and 252° of rotation. Finite element analysis (FEA) validated the compression arm’s mechanical reliability, showing minimal deformation (0.005 mm) under 2.8 Nm of force. To enhance portability and efficiency, additive manufacturing (AM) was utilized to fabricate all of the key components, including the compression arm and tidal volume sensing system. A Generative Design (GD) optimization approach further reduced material usage while maintaining structural integrity, improving weight efficiency without compromising performance. The flexibility of 3D printing allowed for rapid prototyping and design iteration, making the system adaptable to various BVM models. This study demonstrates the potential of automated BVMs to improve emergency ventilation, reduce human error, and enhance patient safety. Future work will focus on exploring applications in pre-hospital and community-based ventilation solutions, similar to public access defibrillators.